ChemInform Abstract: Mild and Metal‐Free Trifluoromethylation and Pentafluoroethylation of gem‐Difluoroalkenes with TMSCF3 and TMSCF2CF3. Issue 2 (23rd December 2015) - Jin, Guanyi; Zhang, Xuxue; Fu, Dan; Dai, Wenpeng; Cao, Song
Abstract: A direct and efficient approach for the trifluoromethylation and pentafluoroethylation of 1, 1‐diaryl‐2, 2‐difluoroethenes with TMSCF3 and TMSCF2 CF3 in the presence of TBAF is developed.